Conocimientos y prácticas sobre prevención y manejo de enfermedad diarreica aguda, en madres de niños/as del Centro de Buen Vivir Blanca Ruiz de Godoy Mies, Loja 2014-2015 - Guamán Chuncho, Mariuxi Elizabeth (2015)
The Acute diarrheal disease is a major cause of infant mortality, annually cause the deaths of nearly one million children worldwide. In this context the present descriptive study, considering the general objective is to determine the maternal knowledge and practices on prevention and management of acute diarrheal disease in children / as attending the Children's Center of Good Living New MIES Blanca Ruiz de Godoy, of the city of Loja 2014-2015; collecting information for the survey, conducted at forty mothers of children treated at the Children's Center was used; the results show that the highest percentage of mothers correctly defined diarrhea, also a significant percentage unknown risk factors and measures that reduce the risk of causing the disease; There is little knowledge of mothers on the management of diarrhea, especially related to symptoms to take the child / to emergency health service or hospital, preparation of homemade ORS, signs of dehydration; unlike previous results mothers correctly identify the warning signs to prevent complications, and preparation of oral rehydration salts .A large group of mothers apply appropriate prevention practices and management, however some mothers do not practice proper disposal wastewater and sewage, maintain domiciliary animal care prior preparation of food intake and the type of liquid that provide after the diarrheal episodio is inadequate Key Words: Knowledge, practice, prevention, management, mothers, diarrheal.